Ermida do Paiva: arquitetura e implantação monástica na serra de Montemuro - Lopes Cunha, Cláudia Gonçalves (Genius Loci: lugares e significados, 2017)
Keywords: ermida do paiva

Ermida do Paiva: Arquitetura e Escultura - Lopes Cunha, Cláudia Gonçalves (University of Porto, 2015)
Keywords: ermida do paiva

Uzos da Igreia da Ermida do Paiva - Carvalhal, Marta; Azevedo, Eufemia (Junta de Freguesia da Ermida, 2013)
Keywords: ermida do paiva

Ermida do Paiva: reflexões e problemáticas - Rosas, Lúcia Maria; Botelho, Maria Leonor; Resende, Nuno (Revista da Faculdade de Letras: Ciências e Técnicas do Património, 2013)
With this article we want to reflect and discuss some of the historical issues concerning the Romanesque architecture, taking as an example the Ermida do Paiva (Castro Daire). Problems like the recovery of medieval heritage, the implantation in the territory or the foundational motivation in Portuguese history context are debated.
Keywords: ermida do paiva

Ermida do Paiva - Backmund, Norbert (Dictionnaire d'histoire et de géographie ecclésiastiques, 1963)
Keywords: ermida do paiva

O templo das siglas, a igreja da Ermida do Paiva - Lacerda, Aarão de (Terra portuguesa : revista ilustrada de arqueologia artistica e etnografia, 1918)
Keywords: ermida do paiva

O templo das siglas, a igreja da Ermida do Paiva - Lacerda, Aarão de (Terra portuguesa : revista ilustrada de arqueologia artistica e etnografia, 1917)
Keywords: ermida do paiva